Echinoderms Metabolites: Structure, Functions and Biomedical Perspectives - Kalinin, Vladimir I. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The materials published in the Special Issue reflect the real diversity of echinoderm metabolites and cover most of their specific classes and biomedical potential as antioxidant, antiviral, anticancer, and even anticoagulant preparations. The metabolites include sea urchin naphtoquinoid pigments and their semi-synthetic derivatives, sea cucumber triterpene glycosides, esters of polyhydroxysteroids from starfish, sea urchins free sterols, and sea cucumber fucosylated chondroitin sulfates. This Special Issue, "Echinoderm Metabolites: Structure, Functions, and Biomedical Perspectives", is a collection of articles about different scientific aspects concerning low molecular weight and biopolymer metabolites from echinoderms, including their isolation and chemical structures, biological activities, biosynthesis and evolution, biological functions, and obtaining of semi-synthetic derivatives of biologically active natural products. This Special Issue includes materials about sea urchin naphtoquinoid pigments and their semi-synthetic derivatives, sea cucumber triterpene glycosides, esters of polyhydroxysteroids from starfish, sea urchin free sterols, and sea cucumber fucosylated chondroitin sulfates.